Antioxidant and Antiproliferative Activities of Methanol Extract from Melaleuca cajuputi subsp. Cumingiana [Turcz.] Fruit - Isnaini Isnaini; Rosinta Dewi Achmadiyah; Gelvia Awaeh; Husnul Khatimah; Alfi Yasmina (Jurnal Sains dan Terapan Kimia, 2023)
Melaleuca cajuputi subsp. Cumingiana [Turcz.] Barlow (M. cajuputi) is a plant that is easily found in Banjarmasin. M. cajuputi contains phytochemical compounds in the form of polyphenols including flavonoids, quinons, saponins, and alkaloids that are thought to have antioxidant and antiproliferation activities. The aim of this research was to find out analyze antioxidant and antiproliferation activity of M. cajuputi fruit methanol extract. The antioxidant activity was tested using the DPPH method. The activities were observed in IC50 and were measured using the UV-VIS spectrophotometer at a wavelength of 517 nm. To test the antiproliferation, true experimental with post-test was applied in this research.  Animal used in this study were 30 mature zebras (length > 2.5 cm) which were grouped into 4, namely the negative control group (DMSO 0.05%), the methanol extract group of M. cajuputi with concentrations of 18.5 ppm, 37 ppm and 74 ppm. The bound variable in this study was antiproliferation activity in the tail of an amputated fish. Data analysis was measured by one-way ANOVA and Post-Hoc Tukey HSD tests. Phytochemical results obtained the presence of phenol compounds, cuinons, flavonoids, alkaloids, saponins, tannins, steroids and terpenoids. Methanol extract of Melaleuca cajuputi subsp Cumingiana [Turcz.] Barlow fruit was at IC50 of 15.50 ppm (95% CI 8.31- 32.72).  The antiproliferation activity of zebrafish tails increased in the administration of fruit extract Melaleuca cajuputi subsp. Cumingiana [Turcz.] Barlow in consentration of 74 ppm (p<0.05), both on day 4 and day 8 of measurement when compared to negative controls. It can be concluded that methanol extract of Melaleuca cajuputi subsp Cumingiana [Turcz.] Barlow fruit has antiproliferative activity against the growth of amputated zebrafish tails.